Il Colegio de España di Bologna e gli studi di diritto internazionale. Un omaggio ad Alfonso-Luis Calvo Caravaca - Davì, Angelo; Zanobetti, Alessandra (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The essay traces the history of the Colegio de España, founded in Bologna in 1364 by Cardinal Albornoz to allow Hispanic students to attend the local law school, which enjoyed a great reputation at the time. The Colegio, one of the oldest university residences founded in the Middle Ages, is one of the few still in function and it hosts Spanish scholarship holders who study in Bologna for two years to prepare their doctoral thesis, most of them specialising in law. The article offers a historical perspective of this famous institution, looking in particular at the studies and subsequent work of the students who have devoted themselves to international law.